A Long-term Retrospective Evaluation of Functional and Radiographic Outcomes of Pediatric Hip Surgery in Hurler Syndrome. Issue 1 (January 2016) - Kennedy, Jim; Noel, Jacques; O'Meara, Anne; Mulhall, Kevin; Crushell, Ellen; Fogarty, Esmond; Kelly, Paula
Abstract : Background: After successful hematopoietic stem cell transplantation, maintaining function and mobility have become key goals in the management of patients with Hurler syndrome, (mucopolysaccharoidosis type 1H). The aim of this study was to establish the functional and radiologic outcomes after hip surgery in patients with this condition who had reached skeletal maturity. Methods: We prospectively followed 13 mucopolysaccharoidosis type 1H patients with closed triradiate cartilages who had undergone hip surgery in a single institution (Our Lady's Children's Hospital, Crumlin) in early childhood, after successful hematopoietic stem cell transplantation. Functional assessment was performed using the Harris Hip Score. Acetabular and femoral head morphology were defined using a pelvic radiograph. Results: The average age at follow-up was 18.6 years (range, 13.2 to 23.8 y). The average length of follow-up from surgical intervention was 14.6 years (range, 10.3 to 21.6 y). The average Harris Hip Score at follow-up was 61.0 (range, 19 to 91). At follow-up, 4 patients were either wheelchair bound or required a walking frame to mobilize in the community. At follow-up, all hips were in-joint with an average center edge angle of 37.7 degrees (range, 0 to 63 degrees). All hips displayed characteristic medial flattening of the femoral head. Ten hips (of 26 hips) showed radiologic degenerative changes with loss of joint space <2 mm. Conclusions: Despite the surgical provision of stable well-covered hips, active intervention did not prevent the development of radiologic deterioration and clinically significant hip arthritis. We recommend that pediatric hip surgery in Hurler syndrome be designed with the possibility of early hip replacement in mind. Level of Evidence: Level III.